2019
DOI: 10.1186/s12917-019-2106-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canine prostate volume in calculated tomographic images - comparison of two assessment methods

Abstract: BackgroundSince most prostatic diseases are associated with the organ’s enlargement, evaluation of prostatic size is a main criterion in the diagnosis of prostatic state of health. While enlargement is a non-uniform process, volumetric measurements are believed to be advantageous to any single dimensional parameter for the diagnosis of prostatomegaly. In a previous study, volume was analysed with a slice addition technique (SAT), which was validated as highly accurate. Irrespective of high accuracy, SAT repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, in one study, it was found that the ellipsoid formula method underestimates the prostate CT volume between 22.4-31.1% when compared with volume measured using a similar technique to OsiriX ® . 28 In the prospective part, there was no consistent bias of the CT volume versus water displacement method, and over 90% of measurements were situated within the 95% LoA (Figure 4). However, some outliers were detected.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, in one study, it was found that the ellipsoid formula method underestimates the prostate CT volume between 22.4-31.1% when compared with volume measured using a similar technique to OsiriX ® . 28 In the prospective part, there was no consistent bias of the CT volume versus water displacement method, and over 90% of measurements were situated within the 95% LoA (Figure 4). However, some outliers were detected.…”
Section: Discussionmentioning
confidence: 86%
“…Another time‐saving method to calculate the volume of the prostate is to use the ellipsoid formula and linear measurements of the prostate, including length, width, and height. However, in one study, it was found that the ellipsoid formula method underestimates the prostate CT volume between 22.4–31.1% when compared with volume measured using a similar technique to OsiriX ® 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prostate volume calculation formula used is a prolate ellipsoid. The formula used to calculate prostate size is height (anteroposterior) x width (transversal) x length (cephalocaudal) x (π / 6) (Haverkamp et al, 2019). Determination of the relationship between serum PSA and prostate volume using the Spearman statistical test with statistical analysis was significant when p <0.05.…”
Section: Resultsmentioning
confidence: 99%
“…The prostate volume calculation formula used is a prolate ellipsoid. The formula used to calculate prostate size is height (anteroposterior) x width (transversal) x length (cephalocaudal) x (π / 6) (Haverkamp et al, 2019…”
Section: Methodsmentioning
confidence: 99%